Demography and burial exclusion in Mycenaean Achaia, Greece - Jones, Olivia A. (Journal of Greek Archaeology, 2018)
The Late Bronze Age period in Greece, known as the Mycenaean period (Figure 1), has been an influential research topic in Greek archaeology since the excavations at Mycenae (Figure 2) by Heinrich Schliemann in the late 19th century. The mortuary record in particular, with exceptional contexts such as the Shaft Graves filled with golden funerary masks, and the elaborately constructed beehive stone-built tholos tombs (pl. tholoi), have encouraged discussions of conspicuous consumption and shifts of power in early Mycenaean (MH III-LH I) Greece.